A Comprehensive Spinal Cord Injury Treatment Protocol Improves Outcomes and Decreases Complications. Issue 5 (May 2023) - Sharon, Melinda; Bardes, James M.; Riley, Holly; Wagner, Afton; Davis, Jennifer Knight; Schaefer, Gregory; Wilson, Alison; Khan, Uzer
Background: Spinal cord injury (SCI) is a devastating event with a complicated recovery. Through the use of an interdisciplinary team a comprehensive care plan was developed, utilizing all available best practices, to prevent secondary complications. Previous work has shown the benefit of single system protocols or interventions. This study aimed to assess changes in outcomes after implementation of a comprehensive protocol. Material and Methods: This was a retrospective cohort study performed at an ACS Level I trauma center. It was based on data abstract from the institutions trauma registry over a 10 year period. Patients with quadriplegia after a traumatic injury were included. Data on hospital outcomes and complications was collected and compared before and after the use of the Spinal cord injury protocol. Results: 58 patients were evaluated. Overall, there was a reduction in complications after the implementation, with significant reductions in pneumonia (47% vs 16%; P = .02) and decubitus ulcers (47% to 11%; P = .005). ICU length of stay decreased by 7 days and hospital length of stay decreased 13 days. There was no difference in mortality. Hospital costs also decreased a mean of $42, 000. Conclusions: A comprehensive SCI protocol can reduce secondary complications in quadriplegic patients. This study found significant decreases in pneumonia and decubitus ulcer rates after implementation of the protocol. Lengths of stay and cost were also significantly reduced. Future research using comprehensive SCI protocols is needed to further assess its effects on outcomes for this specific patient population. Similar centers should consider adoption of comprehensive SCI protocols.